EKOTEOLOGI ISLAM: RESPON DAN SOLUSI AL-QUR’AN TERHADAP FENOMENA GLOBAL WARMING - Nahdha Ibtisam; Quathoniyah Nurul Mahmudah; Teti Mulyani; Ade Nailul Huda (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The news of Global warming is a serious challenge that threatens the sustainability of life on earth. This crisis requires not only technical solutions, but also ethical and spiritual approaches that can foster ecological awareness. This study aims to examine the Qur'anic contribution to the issue of Global warming through the ecotheological approach developed by Mujiyono Abdillah. The method used is qualitative with a library research approach and thematic analysis of Qur'anic verses related to nature and the environment. Abdillah's approach emphasizes the importance of reading the Qur'?n in an ecological way that places humans as caliphs responsible for the preservation of the earth. The results of the study show that the Qur'?n contains the principles of sustainability, balance (m?z?n), prohibition of damage (fas?d), and human responsibility for nature. This study is expected to enrich the discourse of thematic interpretation and encourage the development of Qur'anic ecotheology as a response to contemporary ecological challenges.